THE ROLE OF AI IN ENHANCING ACADEMIC WRITING SKILLS: A NEW METHODOLOGICAL APPROACH FOR PHILOLOGY STUDENTS - Ergasheva Sarvinoz Ahadjon qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
In this article, the opportunities of using artificial intelligence in writing academic text among philology students was analyzed. Instructional functions of AI were organized according to three stages and effective utilization of prompts was examined with examples in order to attain desirable results. The outcomes indicate that, artificial intelligence is not just text generator, it helps students to enhance critical thinking and scientific acumen.